Neopterin as a Surrogate Marker for Coronary Artery Disease in Rheumatoid Arthritis - Maryam K. Khaery; Rana A. Hamdi (مجلة كلية الطب)
Background: Rheumatoid arthritis is an inflammatory illness. A complication of Rheumatoid arthritis is mainly linked to the risk of cardiovascular disease. High body weight has been implicated as a perilous risk factor for the development of Rheumatoid arthritis. Neopterin is secreted by monocytes and macrophages and is highly secreted from the coronary plaque. Moreover, high-sensitivity C-reactive protein is a biochemical analysis applied to quantify C-reactive protein with high sensitivity. Objectives: To evaluate serum Neopterin and high-sensitivity C-reactive protein in patients with rheumatoid arthritis to predict the risk of coronary artery disease. In addition, a correlation between neopterin and high-sensitivity C-reactive protein and anthropometric measures. Methods: The study included 120 women, 60 of whom had rheumatoid arthritis and 60 of whom were controls. Serum analysis included measuring neopterin, determining the sensitivity of C-reactive protein, and estimating anthropometric measurements. Pearson's correlation between two quantitative variables was computed, and a t-test was applied. The correlation coefficient value demonstrates a positive or negative relation. Results: The patients had significantly higher mean values of serum Neopterin, high-sensitivity C-reactive protein, body mass index, waist circumference, and waist-to-hip ratio compared to controls. were detected in the patient group, significant positive correlations were found between serum Neopterin and high-sensitivity C-reactive protein, as well as body mass index, waist circumference, and waist-to-hip ratio. Conclusion: The inflammatory markers neopterin and high-sensitivity C-reactive protein levels are higher in rheumatoid arthritis patients. The higher serum levels of these markers reflected the elevated level of systemic inflammation, and the patient was at risk of coronary artery disease. Also, there is a higher prevalence of obesity and overweight in rheumatoid arthritis patients and a positive correlation between neopterin levels and high anthropometric measures, which reflects an association between Neoperin and risk factors of coronary artery disease.